Intergenerational Social Mobility - Causa, Orsetta (OECD Economics Department Working Papers, 2009)
This paper assesses recent patterns in intergenerational social mobility across OECD countries and examines the role that public policies can play in affecting such mobility. It shows that the relationship between parental or socio-economic background and offspring's educational and wage outcomes is positive and significant in practically all countries for which evidence is available. Intergenerational social mobility is measured by several different indicators since no single indicator provides a complete picture. However, one pattern that emerges is of a group of countries, e.g. southern European countries and Luxembourg, which appears to rank as relatively immobile on most indicators, while another group, e.g. Nordics, is found to be more mobile. Furthermore, public policies such as education and early childcare play a role in explaining observed differences in intergenerational social mobility across countries. In addition, this study also finds a positive cross-country correlation between intergenerational social mobility and redistributive policies